2016
DOI: 10.1073/pnas.1503346113
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor 7-like 1 is involved in hypothalamo–pituitary axis development in mice and humans

Abstract: Aberrant embryonic development of the hypothalamus and/or pituitary gland in humans results in congenital hypopituitarism (CH). Transcription factor 7-like 1 (TCF7L1), an important regulator of the WNT/β-catenin signaling pathway, is expressed in the developing forebrain and pituitary gland, but its role during hypothalamopituitary (HP) axis formation or involvement in human CH remains elusive. Using a conditional genetic approach in the mouse, we first demonstrate that TCF7L1 is required in the prospective hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 68 publications
0
39
0
1
Order By: Relevance
“…For example, in a hypothalamusspecific Shh knockout mouse, a defect in hypothalamic patterning also caused pituitary hypoplasia and absence of the optic disc, consistent with phenotypes in human patients with septo-optic dysplasia (SOD) (Jeong et al, 2006;Zhao et al, 2012). Other evidence shows that the Wnt/β-catenin pathway also plays a clinically relevant role in hypothalamic patterning, as SOD patients with variants in the Wnt effector TCF7L1 have been identified (Gaston-Massuet et al, 2016). Multiple additional genes have been linked to developmental disorders of the hypothalamus that lead to hypopituitarism (Mehta and Dattani, 2008), including SOX2 and SOX3 (Woods et al, 2005;Macchiaroli et al, 2014).…”
Section: Box 1 Hypothalamic Dysfunctionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, in a hypothalamusspecific Shh knockout mouse, a defect in hypothalamic patterning also caused pituitary hypoplasia and absence of the optic disc, consistent with phenotypes in human patients with septo-optic dysplasia (SOD) (Jeong et al, 2006;Zhao et al, 2012). Other evidence shows that the Wnt/β-catenin pathway also plays a clinically relevant role in hypothalamic patterning, as SOD patients with variants in the Wnt effector TCF7L1 have been identified (Gaston-Massuet et al, 2016). Multiple additional genes have been linked to developmental disorders of the hypothalamus that lead to hypopituitarism (Mehta and Dattani, 2008), including SOX2 and SOX3 (Woods et al, 2005;Macchiaroli et al, 2014).…”
Section: Box 1 Hypothalamic Dysfunctionmentioning
confidence: 58%
“…Given conserved Wnt8b expression in the caudal hypothalamus of all vertebrates tested (Lako et al, 1998;Garda et al, 2002;Lee et al, 2006), this posteriorizing function is likely to be conserved in other species. Indeed, when Tcf7l1, which encodes a transcriptional repressor of Wnt targets, is conditionally knocked out in the mouse hypothalamus and pituitary, the developing hypothalamus is posteriorized (Gaston-Massuet et al, 2016). Lhx2, a potential upstream inhibitor of Wnt signaling (Peukert et al, 2011), has also been shown to play a role in the patterning of the telencephalicoptic-hypothalamic field, and to specify SCN neurons at the expense of neuroendocrine fates (Roy et al, 2013).…”
Section: Box 2 Modular Changes In Hypothalamic Anatomy: a Means To Ementioning
confidence: 99%
“…LEF1 is temporally detected in the developing pituitary at E9.0, and reappears at E13.5, but no aberrant pituitary phenotype was observed in Lef1 −/− mice during embryonic development (Olson et al 2006). In contrast, conditional Tcf7l1 knockout affects pituitary development, but coexisting effects at the level of the ventral diencephalon complicate the interpretation of the pituitary phenotype (Gaston-Massuet et al 2016). TCF7L2 may be involved in the repression of Prop1 in embryonic pituitary progenitor cells (Brinkmeier et al 2003(Brinkmeier et al , 2007.…”
Section: :3mentioning
confidence: 99%
“…27,28 We also identified a frameshift in the hypopituitary gene TCF7L1 (p.S15Kfs*41), transmitted from an unaffected mother to her son (RaKi_51), suggesting that this variant, possibly in concert with the de novo mutation in NOBOX, contributes to the CPHD phenotype in her son. 29 In our study we focused on variants that are extremely rare or absent in the large contemporary multiethnic sequencing databases (e.g., gnomAD) (e.g., variants in SLC20A1 and SLC15A4), as we initially argued that a fully penetrant disease genotype should be no more common in the population than the disease that it causes. Likely damaging variants in these two candidate genes were also found in further 2 out of 200 patients, making it extremely likely that the variants are causative from a statistical perspective compared with individuals from the gnomAD server (0/55,607 individuals for the L89S variant of SLC20A1; 0/7506 individuals for the SLC15A4 P456L variant, and no data for the L521F variant of SLC20A1 and L84F variant of SLC15A4).…”
Section: Discussionmentioning
confidence: 99%
“…Both mother and son RaKi_51 carried this rare variant, which is not annotated in the gnomAD database, strongly suggesting that it contributes to function; in the son possibly in concert with a de novo mutation in the NOBOX gene. 29 …”
Section: Inherited Variants Of Known Cphd Genes From Asymptomatic Parmentioning
confidence: 99%